ELECTRONIC SYSTEM FOR DATA ACQUISITION IN AGRICULTURAL MACHINES - MACHADO, ANTÔNIO LILLES TAVARES; TREIN, CARLOS RICARDO; BRITO, RENATO MACHADO DE BRITO (Revista Brasileira de Engenharia de Biossistemas, 2007)
To quantify soil-machine relationship, it is necessary to obtain data which is, at the same timeaccurate, reliable and of easy attainability. This is only gotten through the use of electronicinstrumentation, which should be based on three basic principles: appropriate precision, accessiblecost and good strength. Due to the fact that available instrumentation for agricultural machinesdata acquisition is costly and require high maintenance, the Machines and Agricultural MechanizationSector of the DER-FAEM-UFPel, together with the Electronic Instrumentation Laboratory of theDEE-EE-UFRGS, developed a new system of data acquisition for agricultural machines. The systemdescribed in this work had as main objectives the accuracy, being robust and of easy handling,accessible cost and at the same time of easy maintenance and amplification. The results showedthat the objectives were fully achieved.